Comparative analysis of the views and attitudes of elementary and secondary school pupils from the Czech Republic and Slovak Republic on the division of the Czech and Slovak Federative Republic (ČSFR) - Marcel Lincényi; Matej Mindár (Insights into Regional Development)
This paper addresses current views and attitudes of pupils on the division of the Czech and Slovak Federative Republic (CSFR). The current young generation has not experienced the division of the former common state of Czechs and Slovaks. They thus gain their opinions and knowledge on this issue not only from the school environment, but also from their parents or grandparents. The main research objective was a comparative analysis of the current views and knowledge of selected elementary and secondary school pupils in the Czech Republic and the Slovak Republic on the division of ČSFR into two separate States. Through their research method, the authors identified how selected respondents perceived post-November political processes leading to the constitutional and peaceful division of the Czech and Slovak Federative Republic. One of the positive benefits of their study was the fact that most Slovak and Czech respondents perceived positively the emergence of the independant Slovak and Czech Republics as of 1 January 1993.